Gene expression profiling by microarrays clinical implications - Hofmann, Wolf-Karsten (Cambridge University Press, 2006)
Microarray analysis is a highly efficient tool for assessing the expression of a large number of genes simultaneously, and offers a new means to classify cancer and other diseases. Gene expression profiling can also be used to predict clinical outcome and response to specific therapeutic agents. This survey spans recent applications of microarrays in clinical medicine, covering malignant disease including acute leukaemias, lymphoid malignancies and breast cancer, together with diabetes and heart disease. Investigators in oncology, pharmacology and related clinical sciences, as well as basic scientists, will value this review of a promising new diagnostic and prognostic technology
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Gene expression; Medical genetics; Genexpression; Microarray